“PENGARUH IKLIM KERJA, DISIPLIN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG” (Study Pada Rumah Sakit Islam Sultan Agung Semarang) - Mohammad Zulfan Anas, 13.05.51.0074; Muhaimin, Muhaimin (Students' Journal of Economic and Management, 2018)
Year-on-year development and health services are increasingly showing a better improvement. It is illustrated by the continuous improvement of quality of service and supported by better equipment and pre-facilities.The population in this research is 166 employees of Sultan Agung Hospital Semarang the sample used is 66 respondents. The analysis tool used is Multiple Linear Regression which first tested by using validity and reliability test. The result of the research shows that the working climate influences on the performance of employees at Sultan Agung Semarang Islamic Hospital. The work discipline has an effect on the performance of employees at Sultan Agung Hospital Semarang and Compensation has an effect on the performance of employees at Sultan Agung Semarang Islamic Hospital